(AH-26,ROTH- 801, PURE ZOE PASTE) IN PRESENCE OR ABSENCE OF SMEAR LAYER - A.R FARHAD; A HAVAEI; N KHAJALI; F KARIMI; F POURSINA (Journal of Research in Medical Sciences, 2002)
Introduction. The aim of this study was to assess the sealing ability of three sealers (AH-26,Roth-801, Pure ZOE paste) using bacterial penetration method in static salivary system in the presence or absence of smear layer.
Methods. The canals in 188 human extracted teeth were prepared and in half of the samples the smear layer was removed using EOTA- Naclo. Then, the samples were divided randomly and each experimental group was obturated with single cone gutta percha and of the mentioned sealers. Then the teeth were set up on vials which contained sterilled TSB cultural media. For 90 days the samples were exposed to artificial saliva bacterial suspension and the turbidity of the cultural media was checked twice a day.
Results. The longest mean period of turbidity was seen in AH-26 smear layer absent group (59.21 days) and the shortest mean period of turbidity was seen in pure ZOE paste smear layer present group (18.35 days).
Discussion. The results of this study shows that removal of smear layer enhances the sealing sealers and AH-26 has the best sealing ability amongst the three sealers considered in this experiment.